The psychological state at teachers of physical éducation and sports in light of the Corona pandemic and its relationship to the level of job satisfaction - تومي ناصرالدين; فضل قيس (sports creativity, 2025)
The study aimed to identify the relationship between the psychological state and the level of job satisfaction at teachers of physical éducation and sports in light of the corona pandemic, the researchers followed the descriptive method and the sample of the study consisted of 115 teachers in the middle and secondary stages in the state of TOUGGOURT, who were selected by a comprehensive inventory method, and the data were processed statistically using (T) test and analysis of unilateral variance. The researchers concluded that there is a correlation between psychological state and the level of job satisfaction in light of the Corona pandemic.